1996
DOI: 10.1152/jn.1996.75.4.1503
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced currents with distinct desensitization and Ca2+ dependence in rat trigeminal ganglion cells

Abstract: 1. Whole cell patch-clamp records from cultured rat trigeminal ganglion cells having soma diameters ranging from 20 to 50 microM revealed that capsaicin activated two inward currents and an outward current. At -60 mV, the inward currents could be distinguished by their different peak times, which were 4.2 +/- 3.1 and 41.4 +/- 16.4 (SD) s. 2. Cells with the smallest soma diameters had the largest current densities. 3. The more rapidly activating current had a linear current-voltage relation and a reversal poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
109
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 0 publications
12
109
0
2
Order By: Relevance
“…For GLNVA, the phenolic hydroxy group of the synthetic capsaicin analog nonanoyl-vanillamide is replaced by a glycerol moiety. Simon, 1996c). Moreover, we found that capsaicin can activate one ( Fig.…”
Section: Currents Activated By Capsaicin Olvanil and Glnvamentioning
confidence: 69%
See 3 more Smart Citations
“…For GLNVA, the phenolic hydroxy group of the synthetic capsaicin analog nonanoyl-vanillamide is replaced by a glycerol moiety. Simon, 1996c). Moreover, we found that capsaicin can activate one ( Fig.…”
Section: Currents Activated By Capsaicin Olvanil and Glnvamentioning
confidence: 69%
“…The chamber containing the neurons had a volume of 500 l and was perfused continuously by KH flowing into the chamber at a rate of 6 ml/min (Liu and Simon, 1996c). In addition, capsaicin, olvanil, GLNVA, and capsazepine (Tocris Cookson, St. Louis, MO.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This, combined with the effects of pronounced desensitisation exhibited by the TG neurone preparation (Liu & Simon, 1996a), may have confounded the ability to identify this interesting aspect of piperine pharmacology. We must note, however, that it is also equally plausible that TRPV1 receptors in the trigeminal ganglia may differ from those in recombinant and DRG preparations as has been previously suggested to explain differences in the pharmacology of capsazepine and indeed capsaicin (Liu & Simon, 1996b). We cannot currently explain why piperine, a structurally similar molecule to capsaicin (Figure 1a), which is thought to act at the same site on the receptor (as defined by displacement of [ 3 H]Resiniferatoxin, Szallasi & Blumberg, 1991), should show this greater efficacy.…”
Section: Fn Mcnamara Et Al Effects Of Piperine At Trpv1mentioning
confidence: 88%